2019
DOI: 10.1016/j.jtho.2019.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Afatinib in NSCLC With HER2 Mutations: Results of the Prospective, Open-Label Phase II NICHE Trial of European Thoracic Oncology Platform (ETOP)

Abstract: Introduction: Mutations in erb-b2 receptor tyrosine kinase 2 (HER2) oncogene are observed in approximately 3% of lung adenocarcinomas or mixed tumors with adenocarcinoma component. Activity of various biologically distinct HER2 inhibitors, including the pan-HER inhibitor afatinib, has been reported in several retrospective trials or small series in advanced pretreated NSCLC with HER2 mutations. We report the first prospective evaluation of afatinib for the treatment of this molecularly defined entity. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
80
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(90 citation statements)
references
References 32 publications
3
80
0
1
Order By: Relevance
“…Among small molecule TKIs, afatinib was most widely used in China in recent years, with PFS ranging from 2.9 to 6 months. 20,[24][25][26][27] Poziotinib, neratinib and pyrotinib had similar PFS, with 4.5-5.5 months, 5.5 and 6.4 months, respectively. 9,28,29 Dacomitinib and Osimertinib had weaker effects on this population, either with a short PFS or being invalid in cell line experiments.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Among small molecule TKIs, afatinib was most widely used in China in recent years, with PFS ranging from 2.9 to 6 months. 20,[24][25][26][27] Poziotinib, neratinib and pyrotinib had similar PFS, with 4.5-5.5 months, 5.5 and 6.4 months, respectively. 9,28,29 Dacomitinib and Osimertinib had weaker effects on this population, either with a short PFS or being invalid in cell line experiments.…”
Section: Discussionmentioning
confidence: 94%
“…This could mean that trastuzumab or T‐DM1 might be beneficial to a minority of patients. Among small molecule TKIs, afatinib was most widely used in China in recent years, with PFS ranging from 2.9 to 6 months . Poziotinib, neratinib and pyrotinib had similar PFS, with 4.5–5.5 months, 5.5 and 6.4 months, respectively .…”
Section: Discussionmentioning
confidence: 99%
“…Although the previous case report showed that ERBB2 mutated NSCLC patient could benefit from afatinib treatment, a retrospective study in China suggested that compared with chemotherapy, afatinib was not more beneficial to ERBB2 mutated NSCLC patients . Also, most of the clinical trials, including afatinib, dacomitinib, and neratinib, focused on ERBB2 exon 20 insertion mutations and failed with a low objective response rate of 11%–19% . Two‐phase II studies showed a promising response of poziotinib and pyrotinib in advanced NSCLC with ERBB2 exon 20 mutation.…”
Section: Discussionmentioning
confidence: 99%
“…82 The two phase II studies of afatinib in patients with exon 20 mutation reported disappointing results of disease control rate (DCR) at 71% including one out of seven uPRs, and a progression-free rate at 12-weeks of 54%, respectively. 83,84 In a multinational, retrospective study of afatinib, 3 out of 27 patients with HER-2 exon 20 mutations responded. Overall, two of the responders harboured YVA or VAG insertions and had received previous trastuzumab and pertuzumab.…”
Section: Her-2 Exon 20 Mutation and Amplificationmentioning
confidence: 99%